Never Missing, Never Found - Panitch, Amanda (New York : Random House, 2016)
"Stolen from her family as a young girl, Scarlett is now moving on from the past and starting her summer job at Adventure Time amusement park. When a girl goes missing from the park, it's clear that the past is not done with Scarlett"--.
new ya 2022 spring.
Keywords: Secrets -- Fiction; Human trafficking -- Fiction; JUVENILE FICTION / Social Issues / Dating & Sex; JUVENILE FICTION / Family / Siblings; Missing children -- Fiction; Kidnapping -- Fiction; Families -- Fiction; Young adult fiction